Exclusive Contents and Next Generation Networks - Ganuza, Juan José (2013)
This paper analyzes the interaction between the market of contents and the development of the next generation network (NGN) industry. We assume structural separation between the network and service operators and the comparative advantage of the service operators depends on the access to premium contents. On one side, we analyze how the structure of the market of contents (the scope of exclusivity contracts) may affect deployment and competition in a NGN setting. On the other side, we endogenize the structure of the market of contents given the presence of NGNs, where a content provider can sell contents directly to consumers, by-passing telecom operators (disintermediation, over-the-top content). In this context, we show that exclusivity only occurs when the content is not highly valued by consumers. Finally, the implication of our analysis for the evolution of the telecommunications industry is discussed.